CO hydrogenation to ethanol and higher alcohols over ultrathin CuCoAl nanosheets derived from LDH precursor. (1st February 2023) - Sun, Kai; Song, Faen; Huang, Wenzhan; Tang, Yu; Zhang, Yujie; Zhang, Jian; Wang, Yuanyang; Tan, Yisheng
Graphical abstract: Triply synergetic catalysis of Cu +, Co and surface hydroxyl groups (-OH) over ultrathin CuCoAl nanosheet was responsible for ethanol synthesis from syngas. Highlights: Ultrathin CuCoAl nanosheets were synthesized by AMOST strategy. The ultrathin CuCoAl nanosheets exhibited excellent ethanol selectivity. The formation of CH x derived from CO dissociation and formate hydrodeoxygenation. A triply synergetic catalysis of Cu +, Co and –OH promoted the synthesis of ethanol. Abstract: Ultrathin CuCoAl nanosheets derived from layered double hydroxide (LDH) precursor (1–3 cationic-layers) were successfully synthesized by aqueous miscible organic solvent treatment (AMOST) strategy and performed for ethanol and higher alcohols production via CO hydrogenation. The ultrathin CuCoAl nanosheets (CuCo-LDH-aw) demonstrated a comparatively higher total alcohols (ROH) selectivity of 47.6 %, and the molar fraction of ethanol reached up to 37.5 % among the total alcohols. As revealed by XRD, TEM, SEM, BET and AFM characterizations, the uniform dispersion of CuCo NPs was observed over the ultrathin CuCoAl nanosheets. Moreover, the optimum ultrathin CuCoAl nanosheets exhibited a higher ratio of Cu + /(Cu 0 + Cu + ), which exerted a positive role on non-dissociative CO* insertion CH x intermediates. More significantly, XPS and in situ CO-DRIFT techniques uncovered the formation of CH x intermediates derived from bridge CO dissociation on the metallic Co species and the formate hydrodeoxygenation route, which involved CO* and surface hydroxyl groups (–OH) reaction. Consequently, it was concluded that the triply synergistic effect of Cu +, Co and surface hydroxyl groups (–OH) species contributed to the improvement in ethanol selectivity via CO hydrogenation.